Forensic Audit, Auditor Competency and Emotional Intelligence on Fraud Prevention - Zain, Fiona Lianita; Utami, Endang Sri (Universitas Nusantara PGRI Kediri, 2023)
Research aim: This research aims to find out how forensic audits, auditor competence, and emotional intelligence affect fraud prevention. Design/Methode/Approach: The method used is quantitative by distributing questionnaires to KAP auditors in Yogyakarta. Research Finding: The research results show that forensic auditing and emotional intelligence affect fraud prevention, while auditor competence has no effect. This indicates that the actualization of forensic audits and the emotional intelligence of auditors will form a good preventive pattern in fraud. Meanwhile, fraud prevention is less effective if it relies on auditor competence. Theoretical contribution/Originality: This research contributes to the development of attribution theory to explain individual attitudes in fraud prevention. Practitionel/Policy implication: This research is useful to the advancement of literature in the field of auditing and may become a reference for comparison in future research. Research limitation: The limitation of this research is the limited sample of auditors and variables that are too narrow so research development is needed to obtain more accurate results.